1018Long-term risk of distant metastasis and post-metastasis survival for breast cancer: health record linkage study. (2nd September 2021) - Lord, Sarah; Daniels, Benjamin; Kiely, Belinda; O'Connell, Dianne; Pearson, Sallie-Anne; Beith, Jane; Bulsara, Max; Houssami, Nehmat
Abstract: Background: After early breast cancer (BC) treatment, women need information about long-term prognosis. In this population-based health record linkage study, we assessed the cumulative incidence of distant metastasis (DM) conditional on the DM-free interval; and BC-specific survival post-metastasis. Methods: We included all women diagnosed with non-metastatic BC in the NSW Cancer Registry, 2001-2002. We used linked records from hospitals, dispensed medicines, radiotherapy services and death registrations and applied stringent criteria to determine time to first DM and BC death. Results: 6338 women were included (BC: localised 3885, regional 2453). The 5-year cumulative incidence of DM was 7.4% (95% confidence interval 6.6-8.3) for localised BC; 22.8% (21.2-24.5) for regional BC. For women DM-free at 5 years, it was 5.7% (5.0-6.6); and 11.4% (10.0-13.0) to year 10, respectively. The annual hazard for BC death following localised BC remained lower than that for non-BC causes; for regional BC, it was similar to that for non-BC causes at 8 years. Following DM (N = 1492), BC-specific survival varied widely (median 25 months, interquartile range 6-127). The probability of surviving BC for ≥5 years was 32.0% (29.4-34.7) overall; and 47.1% (42.6-51.5) for those with a DM-free interval >5 years. Conclusions: Women's risk of DM improves over time since diagnosis; and post-metastasis survival is longer for women with later DM. Key messages: Health record linkage methods can be used for conditional risk estimates to inform women who remain DM-free after early BC about their risk of DM in subsequent years; and post-metastasis survival.